PEMANFAATAN KACANG HIJAU SEBAGAI PENGANTI KACANG KEDELAI DALAM PEMBUATAN TEMPE - Nafiah, Azra Nazirah; Wijayanti, Fitria; Rahayu, Putri (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
The purpose of the study was to determine the utilization of green beans as a substitute for soybeans in making tempeh. The method used in this research is the method used in experimental research, with materials and tools in the form of green beans, water, and tempeh yeast. For tools used such as pots, stoves, spoons, tampah, basins, cloth cloth, plastic, toothpicks, and scales. The results of the study provide options and solutions so that tempeh consumed is not only filling but also looks at aspects of its nutritional content, because mung beans are one source of high-protein legumes. The goal is to reduce the fat content of soybeans and replace it with mung beans which are rich in protein, carbohydrates, and vitamins. With the presence of Rhizopus olighporus fungus in the fermentation process of mung bean tempeh, a lactic acid reaction occurs which produces the enzyme amylase which aims to form glucose which is dioxide by microorganisms into lactic acid. This reaction plays a role in increasing the solubility of minerals and the absorption of nutrients by the body.